Histopathological placental lesions in mild gestational hyperglycemic and diabetic women - Rudge, Marilza Vieira Cunha [UNESP]; Lima, Cesar P.; Damasceno, Débora Cristina [UNESP]; Sinzato, Yuri K. [UNESP]; Napoli, Gustavo; Rudge, Cibele Vieira Cunha [UNESP]; Gallego, Franciane Q. [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP] (Biomed Central Ltd., 2011)
Objective: To investigate and compare the incidence of histopathological placental lesions in mild gestational hyperglycemia, gestational diabetes and overt diabetes at term and preterm gestation.Research design and methods: One-hundred-and-thirty-one placental samples were collected from Diabetes mellitus (DM) positive screened patients. Two diagnostic tests, glycemic profile and 100 g oral glucose tolerance test (OGTT) in parallel identified 4 groups normoglycemic, mild gestational hyperglycemia (MGH), gestational DM (GDM) or overt DM (DM). Placental tissue specimens and sections from 4 groups were obtained by uniform random sampling and stained with hematoxylin-eosin.Results: Placentas from MGH group presented 17 types of histopathological change and higher rates of syncytial nodes and endarteritis. GDM placentas presented only nine types of histopathological change, high rates of dysmaturity, low rates of calcification and no syncytial nodes. Overt DM placentas showed 22 types of histopathological change, 21 of which were present in the preterm period. There were histopathological similarities between MGH and DM placentas, but the former exhibited a higher incidence of endarteritis, which has been described as a post-mortem phenomenon.Conclusion: Our results confirmed that the distinct placental changes associated with DM and MGH depend on gestational period during which the diabetic insult occurs. It may reasonably be inferred that subclinical maternal hyperglycemia during pregnancy, as showed in MGH group, is responsible for increased placental endarteritis, a postmortem lesion in the live fetus.
Keywords: gestational diabetes; mild hyperglycemia; placental histopathology